(untitled) (Proceedings of the International Conference on Public Health, 2022)
The current study was the first large-scale study of the functioning level of Sri Lankan Schizophrenia / Psychotic patients and the first-ever study of this patient population by a psychologist and therefore would shed light on the psychological perspectives on this population. Most judgments regarding the level of functioning of schizophrenia patients are derived from Indian studies. India is Sri Lanka’s closest neighbor and therefore most Indian research assumptions are usually generalized to Sri Lanka. Yet the current study reports similarities as well as differences among Sri Lankan Schizophrenia patients when compared to Indian patients. These differences are attributed to the different social composition of Sri Lanka compared to the Indian society, despite the many shared similarities of the two countries. Women appear to have better social functioning compared to men. High rates of prosocial behavior and voting were observed in the sample. 77.5% of the sample reports never engaging in physical activities while 39.5 % reports engaging in religious activities often. The study was conducted with a sample of 200 out-patients (n=200) from the National Institute of Mental Health (NIMH), Sri Lanka. A translated, validated version of the Social Functioning Scale (SFS) was used in the study. A convenient sample was used.